Evaluation of hearing protection used by police officers in the shooting range - Guida, Heraldo Lorena [UNESP]; Taxini, Carla Linhares [UNESP]; Gonçalves, Claudia Giglio De Oliveira; Valenti, Vitor Engrácia [UNESP] (Associação Brasileira de Otorrinolaringologia e Cirurgia Cervicofacial, 2014)
Introduction Impact noise is characterized by acoustic energy peaks that last less than a second, at intervals of more than 1 s. Objective To quantify the levels of impact noise to which police officers are exposed during activities at the shooting range and to evaluate the attenuation of the hearing protector. Methods Measurements were performed in the shooting range of a military police department. An SV 102 audiodosimeter (Svantek) was used to measure sound pressure levels. Two microphones were used simultaneously: one external and one insertion type; the firearm used was a 0.40 Taurus® rimless pistol. Results The values obtained with the external microphone were 146 dBC (peak), and a maximum sound level of 129.4 dBC (fast). The results obtained with the insertion microphone were 138.7 dBC (peak), and a maximum sound level of 121.6 dBC (fast). Conclusion The findings showed high levels of sound pressure in the shooting range, which exceeded the maximum recommended noise (120 dBC), even when measured through the insertion microphone. Therefore, alternatives to improve the performance of hearing protection should be considered.

Introdução O ruído de impacto é caracterizado por apresentar picos de energia acústica de duração inferior a um segundo, em intervalos superiores a um segundo. Objetivo Quantificar os níveis de ruído de impacto a que o policial militar fica exposto durante atividades de tiro com armas de fogo e analisar a atenuação do protetor auricular utilizado. Método As medições foram realizadas no estande de tiros de um Batalhão da Polícia Militar. Para a medição dos níveis de pressão sonora foi utilizado um audiodosímetro modelo SV 102 (Svantek). Foram utilizados dois microfones simultaneamente: um externo e outro tipo inserção, e a arma utilizada foi a pistola calibre 40, da marca Taurus®. Resultados Os valores obtidos no microfone externo foram de 146 dBC (pico) e ruído máximo de 129,4 dBC (fast). Os resultados obtidos no microfone de inserção foram de 138,7 dBC (pico) e ruído máximo de 121,6 dBC (fast). Conclusão Nossos achados evidenciaram elevados níveis de pressão sonora no estande de tiros, que ultrapassaram os limites máximos recomendados (120 dBC), mesmo em medição com microfone de inserção. Portanto, alternativas para melhorar o desempenho da proteção auditiva devem ser consideradas pela equipe de segurança da corporação.
Avaliação da proteção auditiva utilizada por policiais em estande de tiros
Keywords: Medição de ruído; Ruído ocupacional; Polícia; Noise measurement; Noise occupational; Police